SOUND DESIGN TECHNOLOGIES IN ANIMATED FILMS: MODERN METHODS AND APPROACHES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Sound design in animated films facilitates better understanding of the storyline, ensures emotional balance, and enriches the audiovisual experience. This article explores the impact of modern technologies and innovative approaches on sound design and its efficiency in animated films. The findings are practically valuable for sound designers, directors, and producers, contributing to the improvement of audiovisual product quality. Additionally, recommendations are provided on the development prospects of sound technologies and innovative approaches.